Pertanggungjawaban Pidana Penggelapan Dalam Perjanjian Kredit - Felisitas Palan Lamamere; Maria Virginia Jawaina Wotan; Finsensius Samara; Maria Contasya Ingrainin Atitus; Laurensius Kaba Dami; Yohanes Babtisto Seran (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research examines criminal liability related to criminal acts of embezzlement in the context of credit agreements. Embezzlement in credit agreements is a complex issue because it involves aspects of civil and criminal law. The aim of this research is to identify and analyze the criminal liability of embezzlement perpetrators in the context of credit agreements, as well as their impact on the criminal justice system. This research uses a normative legal approach to examine related laws and regulations and relevant court decisions. The data was analyzed qualitatively to gain an in-depth understanding of criminal liability in cases of embezzlement in the context of credit agreements. The research results show that criminal liability in credit agreements can involve various aspects, including breach of contract, falsification of documents, or acts of fraud. In this context, the role of criminal law as a means of upholding justice is important to protect injured parties, including financial institutions or creditors.